Into the metaverse : the essential guide to the business opportunities of the web3 era - Hackl, Cathy, ....- (London : Bloomsbury Business, 2023)
An illuminating insight into the Metaverse - what it is, how it works, and why it will soon be playing a major role in business, technology and society. In Into the Metaverse, Cathy Hackl, a globally recognized futurist and one of the world's first Chief Metaverse Officers, shares her insights on what companies need to do to harness the next iteration of the internet - the metaverse. In this book you'll find a wealth of information on issues such as: - What is the metaverse and what it means for your brand, organization or company - How to make money in the metaverse through understanding the underlying concepts behind it such as gaming, synthetic media, spatial computing and artificial intelligence. - How to lead in the metaverse through industries that are already forging ahead, such as fashion and marketing. - Who should manage the metaverse function within your organization and why some companies should consider creating a role for a Chief Metaverse Officer. - Finally, how to protect the metaverse and action steps you can take towards the future. Essential reading for any executive, Into the Metaverse, will reshape how you think about the internet and its place for those who want to lead successful businesses, today and into the future. If the internet was first used to connect us to information, and then developed into a social media forum to connect people, then Web3, which connects people, places and things, will help enable the successor state to today's mobile internet - the Metaverse. It will bring together and merge our physical and digital lives, and - in the same way that social media upended our lives and our businesses - the Metaverse will shake things up even more. Into the Metaverse is the essential business guide to understanding the ground-breaking technologies that enable this monumental shift and the opportunities it presents from a business and societal perspective.
Keywords: Metaverse